Penerapan Sistem Aplikasi Pegadaian Digital Service Dalam Memudahkan Nasabah Bertransaksi Pada PT. Pegadaian (Persero) UPC Pagelaran - Putri P., Pradhita Salsabila; Supriadi, Yoyon (Jurnal Informatika Kesatuan, 2022)
Pegadaian is a State-Owned Enterprise (BUMN) in Indonesia, which officially has a license to carry out financial institution activities in the form of financing in the form of channeling credit funds to the public on the basis of a pawning law. Pegadaian is a form of non-bank financial institution that has activities to finance the needs of the community, both productive and consumptive. PT. Pegadaian is now beginning to move towards the stage of transformation into a financial company. Changes made by this company by making an application to facilitate customers in the transaction. For example, PT. Pegadaian has launched an application called "Pegadaian Digital Service" to expand its target market. Pegadaian Digital Service application is a digital service in the form of web and mobile-based applications launched by PT. Pegadaian in order to facilitate customers and prospective customers in dealing with Pegadaian without having to come to the Pegadaian outlet. Digital service pawnshop applications can provide services to customers to get clearer information from the products that are in the application. The purpose of this paper is to find out how the system of the Pegadaian Digital Service application, as well as what are the obstacles that occur when this application is used and what are the solutions made to overcome these obstacles at PT Pegadaian UPC Pagelaran. Based on the results of the discussion, it is known that PT Pegadaian (Persero) UPC Performance held various transactions and services with the online system. Keywords : PT. Pegadaian, Pegadaian Digital Service